2006
DOI: 10.1002/jbm.b.30675
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of osteoblast gene expression by mechanically compatible porous Si‐rich nanocomposite

Abstract: Synthesis of a porous bioactive ceramic implant for load bearing applications is a challenging task in maxillofacial and orthopedic surgeries. A novel bioactive resorbable silica-calcium phosphate nanocomposite (SCPC) has recently been introduced as a potential bone graft. In the present study, we employed SCPC to develop a resorbable porous scaffold and analyzed the effects of composition and porosity on the mechanical properties. The ranges of compressive strength and modulus of elasticity of SCPC containing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
50
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 37 publications
(54 citation statements)
references
References 40 publications
4
50
0
Order By: Relevance
“…25 Relative quantification analysis was performed with LightCycler software version 4.0 (Roche, Indianapolis, IN). The concentration ratios of the target genes were calculated by normalizing mRNA for a particular gene against the mRNA of the housekeeping gene b-actin.…”
Section: -24mentioning
confidence: 99%
“…25 Relative quantification analysis was performed with LightCycler software version 4.0 (Roche, Indianapolis, IN). The concentration ratios of the target genes were calculated by normalizing mRNA for a particular gene against the mRNA of the housekeeping gene b-actin.…”
Section: -24mentioning
confidence: 99%
“…[23] Previous studies have demonstrated that the incorporation of inorganic silicon-containing materials into organic scaffolds enhances their bioactivity. [20-21, 60] In addition, scaffold hydrophobicity has also been shown to influence osteogenic differentiation. [25-26, 61] In our prior report, hydrogels were formed by introduction of an inorganic, hydrophobic methacrylated star polydimethylsiloxane (PDMS star -MA) into PEG-DA hydrogels.…”
Section: Introductionmentioning
confidence: 99%
“…We observed that non-gradient PDMS star -PEG hydrogels increased stimulation of osteogenic differentiation of encapsulated MSCs in proportion to PDMS star -MA content [36]. This behavior was attributed to the inorganic, hydrophobic nature of PDMS star -MA, features commonly associated with other bioactive materials [11, 16, 51]. Thus, gradient scaffolds with a gradual change in bioactivity would be exceptionally useful, not only to screen cell-material interactions, but also for the ultimate regeneration of native-like osteochondral tissues which possess a gradual transition from osseous to cartilage tissue.…”
Section: Resultsmentioning
confidence: 99%